IGF-1R inhibition induces schedule-dependent sensitization of human melanoma to temozolomide - Ramcharan, Roger (Oncotarget, 2015)
Prior studies implicate type 1 IGF receptor (IGF-1R) in mediating chemo-resistance. Here, we investigated whether IGF-1R influences response to temozolomide (TMZ), which generates DNA adducts that are removed by O(6)-methylguanine-DNA methyltransferase (MGMT), or persist causing replication-associated double-strand breaks (DSBs). Initial assessment in 10 melanoma cell lines revealed that TMZ resistance correlated with MGMT expression (r = 0.79, p = 0.009), and in MGMT-proficient cell lines, with phospho-IGF-1R (r = 0.81, p = 0.038), suggesting that TMZ resistance associates with IGF-1R activation. Next, effects of IGF-1R inhibitors (IGF-1Ri) AZ3801 and linsitinib (OSI-906) were tested on TMZ-sensitivity, cell cycle progression and DSB induction. IGF-1Ri sensitized BRAF wild-type and mutant melanoma cells to TMZ in vitro, an effect that was independent of MGMT. Cells harboring wild-type p53 were more sensitive to IGF-1Ri, and showed schedule-dependent chemo-sensitization that was most effective when IGF-1Ri followed TMZ. This sequence sensitized to clinically-achievable TMZ concentrations and enhanced TMZ-induced apoptosis. Simultaneous or prior IGF-1Ri caused less effective chemo-sensitization, associated with increased G1 population and reduced accumulation of TMZ-induced DSBs. Clinically relevant sequential (TMZ → IGF-1Ri) treatment was tested in mice bearing A375M (V600E BRAF, wild-type p53) melanoma xenografts, achieving peak plasma/tumor IGF-1Ri levels comparable to clinical Cmax, and inducing extensive intratumoral apoptosis. TMZ or IGF-1Ri caused minor inhibition of tumor growth (gradient reduction 13%, 25% respectively), while combination treatment caused supra-additive growth delay (72%) that was significantly different from control (p < 0.01), TMZ (p < 0.01) and IGF-1Ri (p < 0.05) groups. These data highlight the importance of scheduling when combining IGF-1Ri and other targeted agents with drugs that induce replication-associated DNA damage.